การรับรู้ความสามารถในการเขียนแผนการพยาบาลในการปฏิบัติการพยาบาลพื้นฐาน ของนักศึกษาพยาบาลชั้นปีที่ 2 วิทยาลัยพยาบาลสภากาชาดไทย ปีการศึกษา 2550 - บรรลิขิตกุล, ธัญลักษณ์; สิงหถนัดกิจ, วิไลพร (Thai Red Cross Nursing Journal, 2009)
การวิจัยเชิงพรรณนาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการรับรู้ความสามารถของตนเองในการเขียนแผนการพยาบาล ปัญหาและอุปสรรคในการเขียนแผนการพยาบาล วิธีการจัดการปัญหาและอุปสรรคในการเขียนแผนการพยาบาลของนักศึกษาพยาบาลชั้นปีที่ 2 ปีการศึกษา 2550 วิทยาลัยพยาบาลสภากาชาดไทยที่ขึ้นฝึกวิชาปฏิบัติการพยาบาลพื้นฐาน กลุ่มตัวอย่างเป็นนักศึกษาพยาบาลชั้นปีที่ 2 ปีการศึกษา 2550 วิทยาลัยพยาบาลสภากาชาดไทย ที่ลงทะเบียนเรียนวิชาปฏิบัติการพยาบาลพื้นฐาน จำนวน 146 คน เลือกกลุ่มตัวอย่างแบบเฉพาะเจาะจง เครื่องมือที่ใช้ในการวิจัยประกอบด้วยแบบสอบถาม 1) ข้อมูลทั่วไป 2) ความสามารถในการเขียนแผนการพยาบาล 3) ปัญหาและอุปสรรคในการเขียนแผนการพยาบาล และ 4) วิธีจัดการปัญหาและอุปสรรคในการเขียนแผนการพยาบาล วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา ผลการวิจัยพบว่า นักศึกษาพยาบาลชั้นปีที่ 2 มีคะแนนความสามารถในการเขียนแผนการพยาบาลโดยรวมอยู่ในระดับปานกลาง มีคะแนนเฉลี่ยต่ำสุดในขั้นตอนการวินิจฉัยการพยาบาล นักศึกษาเกือบทั้งหมดรับรู้ว่าตนเองมีปัญหาในการเขียนแผนการพยาบาลในการปฏิบัติการพยาบาล ในด้านการขาดความรู้และทักษะในการเขียนแผนการพยาบาล และรู้สึกไม่ชอบการเขียนแผนการพยาบาลในขั้นตอนการวินิจฉัยการพยาบาลมากที่สุด นักศึกษาใช้วิธีการปรับความรู้สึกหรือคิดทางบวกที่เกี่ยวข้องกับการเขียนแผนการพยาบาลในการปฏิบัติการพยาบาลพื้นฐานมากที่สุด วิธีการจัดการปัญหาและอุปสรรคในการเขียนแผนการพยาบาล พบว่าการเลือกทำงานอดิเรกที่ชอบและการออกกำลังกายหรือบริหารร่างกาย ข้อเสนอแนะจากการวิจัย ควรมีการพัฒนากระบวนการเรียนการสอนทั้งภาคทฤษฎีและปฏิบัติที่เพิ่มระดับความสามารถของนักศึกษาพยาบาลในการเขียนแผนการพยาบาล จัดให้มีทรัพยากรแหล่งข้อมูลต่าง ๆ ที่สนับสนุนการเขียนแผนการพยาบาล ส่งเสริมการใช้การเลือกทำงานอดิเรกที่ชอบ และการออกกำลังกายเพื่อช่วยเพิ่มความสามารถในการเขียนแผนการพยาบาลของนักศึกษาพยาบาล Perception of Ability of Student Nurses at the Thai Red Cross College of Nursing in 2007 in Creating Nursing Care Plans during the Fundamentals of Nursing Practicum This descriptive research was primarily aimed at evaluating the performance of student nurses at the Thai Red Cross College of Nursing in 2007 when they were creating nursing care plans during the Fundamentals of Nursing practicum. It also defines the problems and obstacles they encountered when making these plans, provides solutions to these problems, and compares the effectiveness of each method. The subjects consisted of 146 student nurses that were studying at the Thai Red Cross College of Nursing during 2007. They were recruited using a purposive sampling method. The research instruments included four questionnaires: general data, self-efficacy in making a nursing care plan, problems and obstacles encountered when making a nursing care plan, and ways to solve these problems. The collected data were analyzed using descriptive statistics. The results showed that the nursing students’ performance when making nursing care plans during the Fundamentals of Nursing practicum was moderate, but that one step in the process, nursing diagnosis, obtained a low score. Lack of knowledge and insufficient skills were the main problems when making nursing care plans. This caused student nurses to feel negative when criticizing a nursing diagnosis. Recreation activities and exercise were shown to significantly relieve the problems and obstacles encountered while making nursing care plans. The p-value was 0.05. This study suggests that the teaching-learning process be improved to induce a higher level of performance in student nurses when writing nursing care plans during the Fundamentals of Nursing practicum. In addition, nursing students should be encouraged to undertake recreation activities and exercise to relieve problems and minimize obstacles while making nursing care plans.